"Is your gig any good?" Analysing job quality in the Australian platform-based food-delivery sector. (September 2019) - Goods, Caleb; Veen, Alex; Barratt, Tom
This qualitative industry case study evaluates job quality in the Australian platform-based food-delivery sector, one part of the growing gig economy where workers, as independent contractors, engage in digitally-enabled and controlled work that is remunerated on a piece rate basis. Using a multi-dimensional framework, we draw on worker accounts of economic security, autonomy and enjoyment to assess job quality. This study posits that to achieve a more refined picture of job quality, both objective and workers' subjective understandings of work need to be understood in the context of their respective 'fit' in terms of individual circumstances, labour market alternatives and the broader socio-political context. This multi-level analysis problematises individual accounts that risk overemphasising the positive elements of platform-based work. Moreover, rather than sitting neatly in a Post- or Neo-Fordist extension of job quality, the findings reveal that the gig economy is a new juncture in capitalist production, the consequences of which need to be taken seriously by regulators, scholars, workers and other relevant stakeholders.